2021
DOI: 10.1212/wnl.0000000000011440
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravenous Mesenchymal Stem Cells for Ischemic Stroke

Abstract: ObjectiveTo test whether autologous modified mesenchymal stem cells (MSCs) improve recovery in patients with chronic major stroke.MethodsIn this prospective, open-label, randomized controlled trial with blinded outcome evaluation, patients with severe middle cerebral artery territory infarct within 90 days of symptom onset were assigned, in a 2:1 ratio, to receive preconditioned autologous MSC injections (MSC group) or standard treatment alone (control group). The primary outcome was the score on the modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 39 publications
1
92
0
2
Order By: Relevance
“…The recent clinical reports using MSCs for the treatment of ischemic stroke are summarized in Table 1 . Some studies have reported on the safety and feasibility of BM-MSCs in patients with ischemic stroke injury [ 48 , 49 , 50 , 51 ]. In these clinical trials, patients received intravenous injections of BM-MSCs, and an improvement in neurological functioning was observed, while no treatment-related adverse events were seen.…”
Section: Clinical Application Of Mscs For Neurological Disordersmentioning
confidence: 99%
“…The recent clinical reports using MSCs for the treatment of ischemic stroke are summarized in Table 1 . Some studies have reported on the safety and feasibility of BM-MSCs in patients with ischemic stroke injury [ 48 , 49 , 50 , 51 ]. In these clinical trials, patients received intravenous injections of BM-MSCs, and an improvement in neurological functioning was observed, while no treatment-related adverse events were seen.…”
Section: Clinical Application Of Mscs For Neurological Disordersmentioning
confidence: 99%
“…No significant improvement was observed in a randomized controlled intravenous phase II trial [ 122 ]. In 2021, Chung et al reported that MSC treatment is not associated with improvements in the 3-month modified Rankin score, and their study provided class III evidence that autologous MSCs do not improve 90-day outcomes in patients with chronic stroke [ 123 ].…”
Section: Clinical Trials Of Msc Therapy For Ischemic Strokementioning
confidence: 99%
“…Robust functional improvement was found in patients undergoing the therapy [ 89 ]. Similarly, autologous modified MSC administration was safe and effective in chronic major stroke patients [ 90 ]. Compared to the control group, patients with MSC treatment demonstrated substantial mitigation of lower extremity motor impairments [ 90 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, autologous modified MSC administration was safe and effective in chronic major stroke patients [ 90 ]. Compared to the control group, patients with MSC treatment demonstrated substantial mitigation of lower extremity motor impairments [ 90 ]. Of note, phase I/II clinical trials conducted by Bang et al showed an increase in Barthel’s index 90 days post-stroke when given IV BM-MSCs to patients [ 91 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation